8th Independent Science Panel Meeting, Nairobi, Kenya, 8-9 May 2015 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
In May 2015 the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) held its eight Independent Science Panel meeting in Nairobi, Kenya.